2020
DOI: 10.53894/ijirss.v3i2.31
|View full text |Cite
|
Sign up to set email alerts
|

A brief review on the reaction mechanisms of CO2 hydrogenation into methanol

Abstract: The catalytic reduction of CO2 to methanol is an appealing option to reduce greenhouse gas concentration as well as renewable energy production. In addition, the exhaustion of fossil fuel, increase in earth temperature and sharp increases in fuel prices are the main driving factor for exploring the synthesis of methanol by hydrogenating CO2. Many studies on the catalytic hydrogenation of CO2 to methanol were published in the literature over the last few decades. Many of the studies have presented different cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…6 Qaderi et al have studied the mechanism of the CO 2 hydrogenation reaction, the suggested reaction mechanisms are the "Formate" intermediate formation mechanism, "Reverse water-gas shift" mechanism, and "Trans-COOH" mechanism. 121 A summary of each of the three probable mechanisms is explained in the subsequent sections.…”
Section: Suggested Mechanism Of Methanol Formation From Co 2 and Hmentioning
confidence: 99%
“…6 Qaderi et al have studied the mechanism of the CO 2 hydrogenation reaction, the suggested reaction mechanisms are the "Formate" intermediate formation mechanism, "Reverse water-gas shift" mechanism, and "Trans-COOH" mechanism. 121 A summary of each of the three probable mechanisms is explained in the subsequent sections.…”
Section: Suggested Mechanism Of Methanol Formation From Co 2 and Hmentioning
confidence: 99%
“…164 Nevertheless, this conclusion cannot be applied to all the materials used for this reaction, and the pathway going through the RWGS reaction was also reported. 165 While the reaction pathway strongly depends on the catalytic system, the reaction parameters can also play a crucial role. As an example, the reactivity of (111) facets of palladium and palladium–zinc alloy have highlighted a RWGS pathway and a formate pathway, respectively.…”
Section: Co2 To Methanolmentioning
confidence: 99%
“…Methanol synthesis from syngas or CO 2 using the classic industrial catalyst based on a mixture of metallic copper, ZnO nanoparticles, and alumina (Al 2 O 3 ) as a promoter is a topic that has been discussed and reviewed in several papers in the last two decades. The question then is why another review article? One reason is that the literature on this subject is simply enormous, not surprisingly given that the reaction has been known and used industrially for more than 50 years, and it is not easy to find in a concise and structured report what can be extracted from all these efforts as general and universally accepted messages.…”
Section: Introductionmentioning
confidence: 99%
“…None of these questions are new, and answers can be found from many excellent and rigorous studies in the existing literature or from extensive reviews. It is much more difficult to find a concise, synthetic but exhaustive summary, yet based on clear evidence. If you ask the question to ChatGPT, you will receive this answer: “The active phase in the Cu/ZnO/Al 2 O 3 industrial catalyst for methanol synthesis typically refers to the copper (Cu) component of the catalyst (...).…”
Section: Introductionmentioning
confidence: 99%